Total factor productivity and income distribution: A critical review - Yongbok Jeon (The University of Utah, Department of Economics, 2007)
The aim of the present paper is to critically reappraise the validity and the relevance of the notion of total factor productivity (TFP) as a measure of technological progress. Placing the focus on the role that the neoclassical distribution theory plays in measuring technological progress, we take up the recent revival of the tautology argument (Felipe & McCombie 2003) and the simple results of the capital controversies. First, I argue that the measure of TFP exclusively relies on the marginal productivity theory of distribution through which factors' income shares are linked to their technological progress. Second, it will be shown that the marginal productivity theory of distribution is based on extremely limited theoretical and empirical grounds. Third, therefore, it is concluded that the measure of TFP as a measurement of the contribution made by technical progress to the economic growth has very little to do with the reality.
Keywords: B41; O11; O47; 330; Total Factor Productivity; Marginal Productivity Theory of Distribution; Income Accounting Identity; Capital Controversies